Ulcerative colitis and autoimmune uveitis. Case report - Anna V. Kagramanova; Vladimir E. Tankovskiy; Aleksandra N. Demchenko; Oleg V. Knyazev; Asfold I. Parfenov (Терапевтический архив, 2024)
The article provides information on the pathogenesis, classification and frequency of ophthalmic extra-intestinal manifestations in patients with inflammatory bowel diseases (IBD). A clinical observation of a patient with autoimmune uveitis and IBD is described, demonstrating the importance of early diagnosis of immuno-inflammatory diseases in the implementation of multidisciplinary management of patients with IBD and extraintestinal manidestations. The use of genetically engineered biological drugs helps to control the course of IBD, ophthalmic manifestations and prevents the development of complications.